Tumour seeding of the renal tumour biopsy tract - a histologically under-recognised feature? - Macklin, PS; Verrill, CL; Roberts, ISD; Colling, R; Mark E Sullivan; Webster, GM; David W Cranston; Tapping, CR; Browning, L (Wiley, 2019)
Renal cell carcinoma (RCC) incidence is rising, partly due to incidental detection during imaging performed for other diseases.1 Image-guided, percutaneous renal tumour biopsy (RTB) enables histological classification of small renal masses (< 4 cm), facilitating management decisions, and confirmation of RCC in patients with disseminated disease who might benefit from systemic therapy.